Regional branch-mix, firm size, job growth and job reallocation - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2012)
A growing body of evidence suggests that reallocation of jobs within and across firms and regions and from low to high-educated labour are essential in driving regional economic growth. Each year, many businesses expand and many others contract. New businesses constantly enter, while others gradually disappear. This paper covers analyses of regional employment change investigating the relationship between regional branch composition, firm size, job growth and job reallocation in regional labour markets. The focus are put on different elements of job dynamics, by the creation of new jobs and destruction of old jobs and how these processes develop by job expansion versus job losses within existing firms, and by new establishments versus job losses due to firm closures. Our indicators are drawn from firm-level databases that cover all firms with at least one employee for all regions and sectors of the economy. The indicators cover also the number of employees within each firm including detailed information of their level of education. Among questions to be answered are how branch-mix and firm size affect job growth generally and for high-qualified labour especially, and to what extent new jobs are created by new established firms versus expansions of jobs within existing firms. Tentative results suggest positive relationship between the regional level of branch-mix and job growth, between the level of branch-mix and firm size and thus also between job growth and firm size. The relationship between regional branch-mix and new establishments tend, however, to be negative. Furthermore, there are positive relationship between job growth both within existing firms and in new established firms and job decline within firms and by firm closures, indicating that reallocation of jobs are important for job growth. New jobs by new establishments clearly exceed the number of jobs lost by firm closures, while job losses within existing firms exceed the number of new jobs created by expansion within these firms. However, it is the creation of new jobs within existing firms that contributes most to the supply of new jobs. The results also indicate that reallocation from low to high-educated labour mostly take place in the job processes within existing firms, more than in job reallocation due to new establishments and firm closures. Beyond these main trends there are, however, detected strong regional variations.
Keywords: J21; 330; Regional labour markets; job reallocation; labour mobilty